Neighborhood Isolation and Mortgage Redlining in Milwaukee County - Smith, Michael; Chang, Woojin (My University, 2016)
Housing policy can entrench the disadvantages of segregation in communities. We seek to identify and quantify economic disparities and neighborhood isolation associated with mortgage redlining. Mortgage redlining is a historical practice by which home loans were selectively denied to certain neighborhoods based on demographics using a system of residential security grades. We will quantify neighborhood isolation by applying a segregation index to three socioeconomic variables: home ownership rate, median household income, and median home value. We will repeat these steps for four time points to construct an analysis of neighborhood isolation over time. We will also conduct a series of ANOVA tests to determine if a neighborhood's residential security grade has a significant impact on the variation of the socioeconomic variables.
Includes maps, figures, tables, bibliography
Keywords: Housing; Neighborhood isolation; Mortgage; Milwaukee County